Wetland: Draining mana whenua - Somerville, Alice Te Punga (New Zealand Sociology, 2026)
Māori and Pasifika people in Aotearoa/New Zealand have overlapping interests in the work of sidestepping the settler state, not only for more productive but, let’s face it, for more interesting conversations. Once we turn to see each other, however, how do we articulate our connections and distinctiveness without reinscribing colonial configurations of assimilation or competition? While the term ‘mana whenua’ (‘the people from here’; ‘the people of this place’) speaks to specific indigeneity, a concept that has meaning throughout Te Moananui-a-Kiwa (the Pacific Ocean), the term ‘mana moana’ feels more complicated. In state and institutional contexts, ‘mana moana’ may be a helpful shorthand for ‘the people you otherwise call Pacific or Pasifika’, but in Indigenous contexts, and specifically in Aotearoa, surely ‘mana moana’ would include Māori? Indeed, this article seeks to problematise the relationship between Māori and Pacific scholarly networks in Aotearoa by asking a simple and selfserving question: Must I, as a Māori scholar of Pacific Studies, leave Aotearoa in order to be a Pacific scholar again? Specifically, this article reflects on the process of turning watery land— swamps, rivers, tributaries, reservoirs, aquifers, streams, lakes—into dry, ‘workable’ land for the sake of the settler state. I hope that ‘drainage,’ which has been central to land alienation and has a legacy of devastating environmental effects, might provide a way into a tricky conversation about these slippery terms. Reflecting on how easily we forget that the making of dry land has been a colonial project, responding to long-standing calls from Pacific Studies to decolonise how we understand the relationship between land and water, tracing the emergence at the University of Waikato of ‘Pacific and Indigenous Studies’, and thinking about the sheer liquidity of whenua (land; placenta) in both meanings of the term, I seek to imagine configurations of mana moana that connect rather than drain.